The Variability in Cytocompatibility and Bone Conduction Based on Different Pore Size and Porosity of n-HA/PA66 Composite Scaffolds - Liu, Yiming; Zhang, Rui; Liu, Sirui; Sun, Jingjing; Zhang, Xue; Kang, Peng; Zhang, Ruipu; Yang, Yanyu; Li, Rui (Frontiers in Materials, 2021)
As porous materials, nano-hydroxyapatite/polyamide 66 (n-HA/PA66) composite scaffolds with both desirable bioactivity and good mechanical properties showed great potential to reconstruct the bone defect. Moreover, the pore size and porosity played a key role in the scaffold architecture and cell or bone ingrowth. To investigate the cytocompatibility of different pore size and porosity of n-HA/PA66 composite scaffolds on differentiation and cytocompatibility of osteogenically induced bone marrow-derived mesenchymal stem cells (BMSCs) and bone conduction in repairing the calvarial critical size defect of Sprague-Dawley rats in vivo, we evaluated three kinds of n-HA/PA66 composite scaffolds according to the pore size and porosity in this study (group A: mean pore size was 214 ± 107.3 μm, and more than 70% were arranged in 100–300 μm; group B: material mean pore size was 375 ± 132.2 μm, and about 60% were distributed in 300–500 μm; group C: mean pore size was 533 ± 169.4 μm, and more than 60% were in 400–700 μm). Osteogenically induced BMSCs were seeded in the three types of n-HA/PA66 material and cultured in vitro, and the variability on cell adhesion, growth, proliferation, osteogenic differentiation was analyzed using scanning electron microscopy alkaline phosphatase (ALP) and collagen type I (COL I) immunohistochemical staining, as well as quantitative real-time PCR (qRT-PCR) analysis on the osteogenesis-related gene expression (alkaline phosphatase, COL I), was done. Three group matrices/BMSC composites were implanted into the cranial defect of Sprague-Dawley rats. The differentiations of osteogenesis in vivo were then evaluated by histological and qRT-PCR analysis on mRNA levels of OPG and RANKL after 4 and 8 weeks, respectively. The in vitro and in vivo results showed that the group B n-HA/PA66 scaffold was more suitable for osteogenically induced BMSC proliferation, differentiation in vitro, and bone conduction in vivo than groups A and C, indicating that the porous n-HA/PA66 matrices with a mean pore size of 375 ± 132.2 μm and porosity 77 ± 2.9% have better cell biocompatibility and bone conduction.